Durable concrete, concrete pole and preparation method of concrete pole

The problem of aging and erosion of existing concrete poles is solved by using specific formulas of durable concrete, including polyurethane water dispersions and metal aggregates, and a higher service life and resistance is achieved.

CN119613047APending Publication Date: 2025-03-14GUANGDONG GUANGZE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811798.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing concrete poles are susceptible to external loads and environmental erosion during long-term service, resulting in structural aging, cracks and steel bars corrosion, which cannot meet the needs of structural functions and usage functions, and poses safety hazards.

Method used

A durable concrete is used, and its formulation includes cement, fly ash, mineral powder, sand, gravel, metal aggregate, polyurethane water dispersion, anti-rust agent, water reducing agent and gas induction agent. Through the polyurethane water dispersion, microfibers and films are formed between the hydration product and the metal aggregate, improving the interfacial transition zone performance between the metal aggregate and the base concrete, enhancing bonding and anti-permeability.

Benefits of technology

It effectively extends the service life of cement poles, improves resistance to corrosion and aging, and allows the poles to operate stably in harsh environments, reducing safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180725380000071
    Figure BDA0005180725380000071
  • Figure BDA0005180725380000081
    Figure BDA0005180725380000081
  • Figure BDA0005180725380000082
    Figure BDA0005180725380000082
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses durable concrete, a concrete pole and a preparation method of the concrete pole. Wherein the durable concrete comprises cement, fly ash, mineral powder, sand, gravel, metal aggregate, polyurethane aqueous dispersion, an antirust agent, a water reducing agent, an air entraining agent and water; wherein the metal aggregate is formed by compounding steel ladle slag and iron tailing sand, and the weight ratio of the steel ladle slag to the iron tailing sand is (0.6-0.8): 1. The polyurethane aqueous dispersion forms a continuous polymer film between the hydration product and the metal aggregate, so that the performance of an interface transition area between the metal aggregate and cement, mineral powder, fly ash and other cementing materials is improved, the durability of the concrete is improved, and the service life of an electric pole made of the concrete can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a durable concrete and cement pole and a preparation method thereof. Background Art

[0002] In overhead power lines, poles are mainly responsible for carrying the loads of accessories such as conductors and crossarms, as well as wind loads and floating ice loads. As an important load-bearing structure to ensure the normal operation of the circuit, poles have a special status and importance in the overhead transmission and transformation circuits of power grids, and their structural performance directly affects the safety and reliability of line operation. Due to the complex climate and working conditions faced by power grids during operation, existing concrete poles are difficult to meet the corresponding structural and functional requirements.

[0003] As the existing poles serve for a long time, they are subjected to the continuous accumulation of external loads. Under the influence of environmental erosion, the concrete materials gradually age and suffer various damages, such as cracks on the pole surface, aging of concrete, and rusting of internal steel bars. They can no longer meet the corresponding structural and functional requirements, posing a hidden danger to the safe operation of the power system. Summary of the invention

[0004] In order to improve the durability of concrete poles and extend the service life of the poles, the present application provides a durable concrete and cement pole and a preparation method thereof.

[0005] In the first aspect, the present application provides a durable concrete, which adopts the following technical solution: A durable concrete is prepared from the following raw materials in parts by weight: 35-40 parts of cement, 4.5-6.5 parts of fly ash, 3.5-4.5 parts of mineral powder, 57-59 parts of sand, 80-100 parts of crushed stone, 12-18 parts of metal aggregate, 2-4 parts of polyurethane aqueous dispersion, 0.6-0.8 parts of rust inhibitor, 0.4-0.6 parts of water reducer, 0.35-0.45 parts of air entraining agent, 16-18 parts of water; The metal aggregate is compounded by ladle slag and iron tailings sand, and the weight ratio of the ladle slag to the iron tailings sand is (0.6-0.8):1.

[0006] By adopting the above technical scheme, after the polyurethane aqueous dispersion is added to the cement-based material, as the cement hydration reaction continues, the polyurethane aqueous dispersion dispersed in the mixture is continuously deposited on the surface of the hydration product and the unhydrated cement particles, and finally forms continuous microfibers and films between the hydration product and the metal aggregate, wrapping the metal aggregate particles bonded thereto, and bridging the pores and cracks inside the concrete, so that the interface transition zone performance between the metal aggregate and cement, mineral powder, fly ash and other cementitious materials is improved, and the metal aggregate and the base concrete show high compatibility, and enhance the bonding performance and anti-penetration performance between the metal aggregate and the base concrete, thereby effectively extending the service life of the cement pole. Among them, the compound use of ladle slag and iron tailings sand, the combination of the two materials provides better physical and chemical stability, and reduces the erosion and wear of concrete in harsh environments. At the same time, the ladle slag and iron tailings sand are compounded according to a certain weight ratio, which helps to achieve the best filling effect of the metal aggregate, thereby improving the density and strength of the concrete.

[0007] Preferably, the raw materials for preparing the polyurethane aqueous dispersion include polyether polyol, hexamethylene diisocyanate and chain extender, and the weight ratio of the polyether polyol, hexamethylene diisocyanate and chain extender is (1-1.5): (1.5-2.5): 0.2.

[0008] Preferably, the polyether polyol is compounded by polytetramethylene glycol, polyethylene glycol and polypropylene glycol, and the weight ratio of polytetramethylene glycol, polyethylene glycol and polypropylene glycol is (1-2): (0.5-1): (0.5-1).

[0009] By adopting the above technical solution, the polyurethane aqueous dispersion and the hydration products of cement penetrate each other to form a three-dimensional polymer network structure, thereby improving the pore structure of concrete, increasing the density of concrete, reducing the penetration channels of water and corrosive media, and thus improving the durability of concrete.

[0010] Preferably, the preparation method of the polyurethane aqueous dispersion is: First, polytetrahydrofuran ether diol, polyethylene glycol and polypropylene glycol are uniformly mixed at 45-55° C., hexamethylene diisocyanate and a catalyst are added under the protection of nitrogen, and the mixture is reacted at 60-70° C. for 1-2 hours to obtain a prepolymer; then, a chain extender and acetone are added to the prepolymer, the mixture is reacted for 1-2 hours, and a neutralizer is added to neutralize the mixture for 30-45 minutes; after the neutralization is completed, the temperature is lowered to room temperature, and the acetone is removed by vacuuming; finally, deionized water is added for dispersion, and the mixture is vigorously dispersed at a stirring speed of 1800-2000 r / min for 30-45 minutes to obtain a polyurethane aqueous dispersion; The catalyst is dibutyltin dilaurate, the chain extender is ethylenediamine, and the neutralizer is triethylamine.

[0011] By adopting the above technical solution, three polyether polyols and hexamethylene diisocyanate are used to prepare polyurethane water dispersion, and the dispersion is added to concrete, which can improve the pore structure of concrete and enhance the durability of concrete. Adding acetone during the reaction can reduce the viscosity of the reaction system, and adding a neutralizer can fully ionize the polyurethane, which is convenient for subsequent reactions.

[0012] Preferably, the rust inhibitor is one or more of sodium benzoate, sodium nitrite and calcium nitrite.

[0013] By adopting the above technical solution, adding rust inhibitor can improve the rust resistance of concrete itself, thereby slowing down the corrosion of steel bars inside the concrete. The rust inhibitor can react with SO4 2- 、C1 - Mg 2+ NH4 + It can also prevent corrosive substances from penetrating or diffusing into the concrete, thereby reducing their direct impact on the steel bars and improving the concrete's own anti-rust ability.

[0014] Preferably, the water reducing agent is a polycarboxylate water reducing agent.

[0015] By adopting the above technical solution, the addition of polycarboxylate water reducer can reduce the number of capillaries, improve the pore structure, and enhance the density of concrete, thereby reducing the penetration rate of chloride ions, delaying the corrosion rate, and improving the corrosion resistance of concrete.

[0016] Preferably, the air entraining agent is at least one of lignin sulfonate, rosin thermal polymer, and triptolide saponin.

[0017] By adopting the above technical solution, the addition of air-entraining agent significantly reduces the surface tension of water, so that many tiny independent closed bubbles are generated during the concrete mixing process. Due to the barrier effect of the bubbles, the evaporation path of free water in the concrete mixture becomes tortuous, small and dispersed, thereby changing the number and characteristics of capillaries, significantly improving the freeze-thaw resistance of concrete after hardening, reducing the possibility of damage to the internal structure of concrete, and at the same time hindering the penetration of corrosive media such as external chloride ions.

[0018] Preferably, the sand is river sand with a fineness modulus of 2.2-1.8, the crushed stone is continuously graded crushed stone with a particle size of 5-15 mm, and the fly ash is fly ash with a specific surface area of ​​3200-3600 cm 2 / g of secondary fly ash.

[0019] By adopting the above technical solution and selecting sand and gravel of appropriate particle size, the pore structure of concrete is further optimized, reducing the penetration channels of moisture and harmful substances, thereby improving the anti-permeability of concrete. The micro-aggregate effect produced by fly ash can fill the voids in cement and greatly improve the particle grading of cement.

[0020] In the second aspect, the present application provides a cement pole, which adopts the following technical solution: A cement pole is made from the durable concrete.

[0021] By adopting the above technical scheme, cement poles are prepared with the durable concrete of the present application. The concrete itself has excellent anti-corrosion effect and can also prevent the steel bars inside it from being corroded. Therefore, it can be used in severe erosion environments such as acid rain, saline-alkali land, deicing salt, frequent freeze-thaw, and coastal areas, and can effectively extend the service life of the poles.

[0022] In a third aspect, the present application provides a method for preparing a cement pole, which adopts the following technical solution: A method for preparing a cement pole comprises the following steps: (1) The steel bars that have been treated with rust prevention are made into a steel bar skeleton and placed in a mold; (2) weighing raw materials according to the component proportions, adding sand, crushed stone and metal aggregate into a mixer, premixing for 2-3 minutes, then adding cement, fly ash and mineral powder into the mixer for dry mixing for 2-3 minutes, and finally adding polyurethane aqueous dispersion, rust inhibitor, water reducing agent, air entraining agent and water into the mixer, and continuing to stir for 20-40 minutes to obtain mixed concrete; (3) The mixed concrete prepared in step (2) is accurately weighed according to the amount required for the electric pole and accurately distributed through a delivery pump, and compacted by a centrifugal process. The electric pole after centrifugation is placed in a steaming and curing tank and left to stand for 3-5 hours to allow the concrete to reach an initial setting state; steam is then introduced into the tank at a heating rate of ≤25°C / h; the temperature in the tank is raised to 75-85°C, and the constant temperature is maintained for 4-6 hours, and then the steam is stopped. After 2-4 hours, the steaming and curing tank cover is opened to start natural cooling. When the mold temperature drops to a temperature difference of no more than 30°C from the ambient temperature, the electric pole mold is opened and demolding is performed; after demolding, the electric pole is subjected to watering and moisture-maintaining maintenance for not less than 7 days to obtain a cement electric pole.

[0023] By adopting the above technical solution, the cement poles prepared by the durable concrete of the present application have better corrosion resistance and anti-aging performance, and effectively extend the service life of the cement poles.

[0024] This application has the following beneficial effects: In the present application, after the polyurethane aqueous dispersion is added to the cement-based material, as the cement hydration reaction continues, the polyurethane aqueous dispersion dispersed in the mixture is continuously deposited on the surface of the hydration product and the unhydrated cement particles, and finally forms continuous microfibers and films between the hydration product and the metal aggregate, wrapping the metal aggregate particles bonded thereto, and bridging the pores and cracks inside the concrete, so that the interface transition zone performance of the metal aggregate and cement, mineral powder, fly ash and other cementitious materials is improved, and the metal aggregate and the base concrete show high compatibility, and enhance the bonding performance and anti-penetration performance between the metal aggregate and the base concrete, thereby effectively extending the service life of the cement pole. Among them, the compound use of ladle slag and iron tailings sand, the combination of the two materials provides better physical and chemical stability, and reduces the erosion and wear of concrete in harsh environments. At the same time, the ladle slag and iron tailings sand are compounded according to a certain weight ratio, which helps to achieve the best filling effect of the metal aggregate, thereby improving the density and strength of the concrete. DETAILED DESCRIPTION

[0025] Preparation Example Preparation Example 1 Preparation of polyurethane aqueous dispersion: First, at 45°C, 0.5kg of polytetrahydrofuran ether diol (Lanabai 25190-06-1), 0.25kg of polyethylene glycol (Jinhao 25322-68-3), and 0.25kg of polypropylene glycol (Haishahua 25322-69-4) were mixed evenly, and under the protection of nitrogen, 1.5kg of hexamethylene diisocyanate and 0.04kg of dibutyltin dilaurate were added, and the mixture was reacted at 60°C for 1h to obtain a prepolymer; then, 0.2kg of ethylenediamine and 0.5kg of acetone were added to the prepolymer, and the reaction was continued for 1h, and then 0.02kg of triethylamine was added for neutralization reaction for 30min; after the neutralization was completed, the temperature was lowered to room temperature, 4kg of deionized water was added for dispersion, and the mixture was vigorously dispersed at a stirring speed of 1800r / min for 30min to obtain a polyurethane aqueous dispersion.

[0026] Preparation Example 2 Preparation of polyurethane aqueous dispersion: First, at 55°C, 1kg of polytetrahydrofuran ether diol (Lanabai 25190-06-1), 0.5kg of polyethylene glycol (Jinhao 25322-68-3), and 0.5kg of polypropylene glycol (Haishahua 25322-69-4) were mixed evenly, and under the protection of nitrogen, 2.5kg of hexamethylene diisocyanate and 0.05kg of dibutyltin dilaurate were added, and the mixture was reacted at 70°C for 2h to obtain a prepolymer; then, 0.2kg of ethylenediamine and 0.5kg of acetone were added to the prepolymer, and the reaction was carried out for 2h, and then 0.03kg of triethylamine was added for neutralization reaction for 45min; after the neutralization was completed, the temperature was lowered to room temperature, 5kg of deionized water was added for dispersion, and the mixture was vigorously dispersed at a stirring speed of 2000r / min for 45min to obtain a polyurethane aqueous dispersion.

[0027] Preparation Example 3 The difference between this preparation example and preparation example 2 is that an equal amount of polycaprolactone diol (average molecular weight 2000) is used instead of polyethylene glycol.

[0028] Preparation Example 4 The difference between this preparation example and preparation example 2 is that an equal amount of polytetramethylene glycol (Lanabai 25190-06-1) is used to replace polyethylene glycol and / or polypropylene glycol. Example

[0029] Example 1 A durable concrete comprises the following raw materials: 35 kg cement (Conch brand ordinary Portland cement with a strength grade of PO 42.5), 4.5 kg fly ash (with a specific surface area of ​​3200 cm 2 / g), 3.5kg mineral powder, 57kg sand (fineness modulus 2.2), 80kg crushed stone, 4.8kg ladle slag (the slag from the converter during steelmaking and the slag produced during the alloying process), 8kg iron tailings sand, 2kg polyurethane aqueous dispersion (prepared in Preparation Example 1), 0.6kg sodium benzoate, 0.4kg polycarboxylate water reducer (Huaxuan High-tech KH-4), 0.35kg calcium lignin sulfonate (Kimik 8061-52-7), and 16kg water.

[0030] The method for preparing the cement pole in this embodiment includes the following steps: (1) The steel bars that have been treated with rust prevention are made into a steel bar skeleton and placed in a mold; (2) weighing raw materials according to the component proportions, adding sand, gravel, ladle slag, and iron tailings sand into a mixer, premixing for 2 minutes, then adding cement, fly ash, and mineral powder into the mixer for dry mixing for 2 minutes, and finally, adding polyurethane aqueous dispersion, sodium benzoate, polycarboxylate water reducer, calcium lignin sulfonate, and water into the mixer, and continuing to stir for 20 minutes to obtain mixed concrete; (3) The mixed concrete prepared in step (2) is accurately weighed according to the required amount of the electric pole and accurately distributed through a delivery pump, and compacted by a centrifugal process. The electric pole after centrifugation is placed in a steaming and curing tank and left to stand for 3 hours to allow the concrete to reach an initial setting state; steam is then introduced into the tank at a heating rate of 25°C / h; the temperature in the tank is raised to 75°C, maintained at a constant temperature for 4 hours, and then the steam is stopped. After 2 hours, the steaming and curing tank cover is opened to start natural cooling. When the mold temperature drops to 25°C, the electric pole mold is opened and demolding is performed; after demolding, the electric pole is subjected to 7 days of watering and moisture-maintaining maintenance to obtain a cement electric pole.

[0031] Example 2 A durable concrete comprises the following raw materials: 37 kg cement (Conch brand ordinary Portland cement with a strength grade of PO 42.5), 5.5 kg fly ash (with a specific surface area of ​​3400 cm 2 / g), 4kg mineral powder, 58kg sand (fineness modulus 2.0), 90kg crushed stone, 6.3kg ladle slag (the slag from the converter during steelmaking and the slag produced during the alloying process), 9kg iron tailings sand, 3kg polyurethane aqueous dispersion (prepared in Preparation Example 1), 0.7kg sodium nitrite, 0.5kg polycarboxylate water reducer (Huaxuan High-tech KH-4), 0.4kg rosin thermal polymer, and 17kg water.

[0032] The method for preparing the cement pole in this embodiment includes the following steps: (1) The steel bars that have been treated with rust prevention are made into a steel bar skeleton and placed in a mold; (2) weighing raw materials according to the component proportions, adding sand, gravel, ladle slag, and iron tailings sand into a mixer, premixing for 3 minutes, then adding cement, fly ash, and mineral powder into the mixer for dry mixing for 3 minutes, and finally, adding polyurethane aqueous dispersion, sodium nitrite, polycarboxylate water reducer, rosin thermal polymer, and water into the mixer and continuing to stir for 30 minutes to obtain mixed concrete; (3) The mixed concrete prepared in step (2) is accurately weighed according to the required amount of the electric pole and accurately distributed through a delivery pump, and compacted by a centrifugal process. The electric pole after centrifugation is placed in a steaming and curing tank and left to stand for 4 hours to allow the concrete to reach an initial setting state; steam is then introduced into the tank at a heating rate of 25°C / h; the temperature in the tank is raised to 80°C, maintained at a constant temperature for 5 hours, and then the steam is stopped. After 3 hours, the steaming and curing tank cover is opened to start natural cooling. When the mold temperature drops to 25°C, the electric pole mold is opened and demolding is performed; after demolding, the electric pole is subjected to 7 days of water sprinkling and moisture-maintaining maintenance to obtain a cement electric pole.

[0033] Example 3 A durable concrete comprises the following raw materials: 40 kg cement (Conch brand ordinary Portland cement with a strength grade of PO 42.5), 6.5 kg fly ash (with a specific surface area of ​​3600 cm 2 / g), 4.5kg ore powder, 59kg sand (fineness modulus 1.8), 100kg crushed stone, 8kg ladle slag (using the slag from the converter when tapping steel and the slag produced during the alloying process), 10kg iron tailings sand, 4kg polyurethane aqueous dispersion (prepared in Preparation Example 2), 0.8kg calcium nitrite, 0.6kg polycarboxylate water reducer (Huaxuan High-tech KH-4), 0.45kg triterpenoid saponin, and 18kg water.

[0034] The method for preparing the cement pole in this embodiment includes the following steps: (1) The steel bars that have been treated with rust prevention are made into a steel bar skeleton and placed in a mold; (2) weighing the raw materials according to the component proportions, adding sand, gravel, ladle slag, and iron tailings sand into a mixer, premixing for 3 minutes, then adding cement, fly ash, and mineral powder into the mixer for dry mixing for 3 minutes, and finally adding polyurethane aqueous dispersion, sodium nitrite, polycarboxylate water reducer, triterpenoid saponin, and water into the mixer and continuing to stir for 30 minutes to obtain mixed concrete; (3) accurately weighing the mixed concrete prepared in step (2) according to the amount required for the electric pole and conveying it through a conveyor The pump is used for precise material distribution, and the centrifugal process is used for dense molding. The poles completed by centrifugation are placed in a steaming and curing tank and left to stand for 4 hours to allow the concrete to reach an initial setting state. Steam is then introduced into the tank at a heating rate of 25°C / h. The temperature in the tank is raised to 85°C, and after maintaining the constant temperature for 5 hours, the steam is stopped. After 3 hours, the cover of the steaming and curing tank is opened to start natural cooling. When the mold temperature drops to 25°C, the pole mold is opened for demoulding. After demoulding, the pole is subjected to 7 days of watering and moisturizing maintenance to obtain a cement pole.

[0035] Example 4 The difference between this embodiment and embodiment 2 is that the polyurethane aqueous dispersion adopts the polyurethane aqueous dispersion prepared in preparation example 3.

[0036] Example 5 The difference between this embodiment and embodiment 2 is that the polyurethane aqueous dispersion adopts the polyurethane aqueous dispersion prepared in preparation example 4.

[0037] Comparative Example Comparative Example 1 A durable concrete, which differs from Example 2 in that an equal amount of copper slag is used instead of ladle slag.

[0038] Comparative Example 2 A durable concrete, which differs from Example 2 in that an equal amount of copper slag is used instead of iron tailings sand.

[0039] Comparative Example 3 A durable concrete, which is different from Example 2 in that ladle slag and iron tailings are not added.

[0040] Comparative Example 4 A durable concrete, which is different from Example 2 in that no polyurethane aqueous dispersion is added.

[0041] Comparative Example 5 A durable concrete, which is different from Example 2 in that an equal amount of styrene acrylate emulsion is used instead of polyurethane aqueous dispersion.

[0042] Performance testing 1. Water absorption rate: The concrete water absorption rate test is carried out in accordance with the water absorption rate test in the "Test Procedure for Polymer Modified Cement Mortar" (DL / T 5126-2021). The specimens are cured to 14 days and 28 days respectively, and then dried in a drying oven for 48 hours, weighed using a precision electronic scale, and then immersed for another 48 hours. The upper surface is greater than 50 mm from the water surface, and then wiped dry and weighed (the drying time is controlled to be the same).

[0043] 2. Chloride ion penetration resistance test: The rapid test method for chloride ion migration (RCM) is used. The test refers to the chloride ion penetration resistance coefficient D in the "Standard for Long-term Performance and Durability Test Methods of Ordinary Concrete". RCM The test was conducted using ф100mm×50mm specimens, with 3 specimens in a group. One group of specimens was tested at each age. The arithmetic mean of the results of each group of 3 specimens was taken as the D RCM Measured value, unit 10 -12 m 2 / s. The results of chloride ion diffusion coefficient are recorded in Table 1.

[0044] The chloride ion diffusion coefficient is calculated as follows: Where D RCM ——Chloride ion diffusion coefficient of concrete measured by RCM method (m 2 / s); T——temperature (K); H——test piece height (m); X d ——Chloride ion color development depth (m); t——power-on test time (s); ——Auxiliary variables:

[0045] 3. Sulfate dry-wet cycle resistance: Select 5% by mass Na2SO4 and 5% by mass MgSO4 solution as test solutions. According to the Standard for Long-term Durability Test Methods of Ordinary Concrete (GB / T 50082-2009), immerse the specimen in a sulfate solution for 15 hours at a temperature of 25-30°C, then take out the specimen and place it in the air to dry naturally for 2 hours, then dry the specimen at 80±5°C for 6 hours, and finally cool the specimen in the air at 25-30°C for 2 hours. The above is one sulfate dry-wet cycle test. When the test reaches the specified number of dry-wet cycles or the strength loss rate of the specimen reaches 25%, stop the dry-wet cycle test. Record the apparent morphology, mass loss rate, and compressive strength of the specimen.

[0046] 4. Salt freeze-thaw cycle resistance: The freeze-thaw cycle test method refers to the "Standard for Long-term Durability Test Methods of Ordinary Concrete" (GB / T 50082-2009), and the "quick freezing method" in the antifreeze test is implemented. The test is carried out using a rapid freeze-thaw test machine. The prepared 5% Na2SO4 solution and 5% MgSO4 solution are respectively injected into the specimen box, and then the test specimen is placed in the specimen box so that the specimen is about 2 cm away from the liquid surface. During the freeze-thaw cycle, each freeze-thaw cycle is completed within (2-4) hours, and the melting time must not be less than 1 / 4 of the entire freeze-thaw time. The freezing temperature of the specimen is -15°C and the melting temperature is 10°C; the test is stopped when the test reaches the specified number of freeze-thaw cycles or the mass loss rate of the specimen reaches 5% or the strength loss rate of the specimen reaches 25%. The apparent morphology, mass loss rate, and compressive strength of the specimen are recorded.

[0047] Table 1 Table 2 According to Example 2 and Comparative Examples 1-2 and combined with the data in Table 1-2, it can be seen that the combination of ladle slag and iron tailings sand provides better physical and chemical stability, reducing the erosion and wear of concrete in harsh environments. In addition, it helps to achieve the best filling effect of metal aggregates, thereby improving the durability of concrete. The electric poles made of this concrete can be used in severe erosion environments such as saline-alkali land, deicing salt, frequent freeze-thaw, and coastal areas, and can effectively extend the service life of the electric poles.

[0048] According to Example 2 and Comparative Example 3 and in combination with the data in Table 1-2, it can be seen that the addition of metal aggregate has a certain inhibitory effect on the multi-factor (load, chemical corrosion, freeze-thaw cycle, etc.) damage of the pole, and the addition of metal aggregate can improve the density of concrete, thereby slowing down the erosion of concrete by corrosive media and effectively enhancing the durability of concrete.

[0049] According to Example 2 and Comparative Examples 4-5 and the data in Table 1-2, it can be seen that when the polyurethane water dispersion is added to the concrete, a dense cross-linked structure is formed inside the concrete due to the cross-linking between the polyurethane molecules, which enhances the bonding force and makes the concrete difficult to be damaged. At the same time, due to the existence of the cross-linked structure inside the concrete, it is difficult for the external corrosive medium to enter the pores inside the concrete, so that the concrete has low water absorption and high impermeability, and the corrosion resistance of the concrete is improved. It can be used to make electric poles to cope with complex climate and working conditions and extend the service life of the electric poles.

[0050] According to Example 2 and Example 4 combined with the data in Table 1-2, the water resistance of polyester polyol is worse than that of polyether polyol, and the polyurethane aqueous dispersion prepared by polyester polyol is added to concrete, which does not significantly improve the durability of concrete. On the contrary, since the ether bond (-O-) in the structure of polyether polyol has a lower cohesive energy and better hydrolysis resistance, the prepared polyether polyurethane aqueous dispersion is added to concrete, which can make the concrete have better anti-seepage performance, thereby slowing down the erosion of corrosive media on concrete.

[0051] According to Example 2 and Example 5 combined with the data in Table 1-2, it can be seen that the polyurethane aqueous dispersion prepared by compounding three polyether polyols (polytetramethylene glycol, polyethylene glycol and polypropylene glycol) has a more obvious improvement effect on the durability of concrete, the degree of cross-linking between the three polymers is higher, and continuous microfibers and films are formed between the hydration product and the metal aggregate, so that the compatibility between the metal aggregate and the base concrete is optimized.

[0052] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A durable concrete, characterized in that: The invention is prepared from the following raw materials by weight: 35-40 parts of cement, 4.5-6.5 parts of fly ash, 3.5-4.5 parts of mineral powder, 57-59 parts of sand, 80-100 parts of crushed stone, 12-18 parts of metal aggregate, 2-4 parts of polyurethane aqueous dispersion, 0.6-0.8 parts of rust inhibitor, 0.4-0.6 parts of water reducer, 0.35-0.45 parts of air entraining agent, 16-18 parts of water; The metal aggregate is compounded by ladle slag and iron tailings sand, and the weight ratio of the ladle slag to the iron tailings sand is (0.6-0.8):

1.

2. A durable concrete according to claim 1, characterized in that: The raw materials for preparing the polyurethane aqueous dispersion include polyether polyol, hexamethylene diisocyanate and chain extender, and the weight ratio of the polyether polyol, hexamethylene diisocyanate and chain extender is (1-1.5): (1.5-2.5): 0.

2.

3. A durable concrete according to claim 2, characterized in that: The polyether polyol is prepared by compounding polytetramethylene glycol, polyethylene glycol and polypropylene glycol, and the weight ratio of the polytetramethylene glycol, polyethylene glycol and polypropylene glycol is (1-2): (0.5-1): (0.5-1).

4. A durable concrete according to claim 3, characterized in that: The preparation method of the polyurethane aqueous dispersion is: First, polytetrahydrofuran ether diol, polyethylene glycol and polypropylene glycol are uniformly mixed at 45-55° C., hexamethylene diisocyanate and a catalyst are added under the protection of nitrogen, and the mixture is reacted at 60-70° C. for 1-2 hours to obtain a prepolymer; then, a chain extender and acetone are added to the prepolymer, the mixture is reacted for 1-2 hours, and a neutralizer is added to neutralize the mixture for 30-45 minutes; after the neutralization is completed, the temperature is lowered to room temperature, and the acetone is removed by vacuuming; finally, deionized water is added for dispersion, and the mixture is vigorously dispersed at a stirring speed of 1800-2000 r / min for 30-45 minutes to obtain a polyurethane aqueous dispersion; The catalyst is dibutyltin dilaurate, the chain extender is ethylenediamine, and the neutralizer is triethylamine.

5. The durable concrete according to claim 1, characterized in that: The rust inhibitor is one or more of sodium benzoate, sodium nitrite and calcium nitrite.

6. The durable concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent.

7. The durable concrete according to claim 1, characterized in that: The air entraining agent is at least one of lignin sulfonate, rosin thermal polymer and triptolide saponin.

8. The durable concrete according to claim 1, characterized in that: The sand is river sand with a fineness modulus of 2.2-1.8, the crushed stone is continuously graded crushed stone with a particle size of 5-15 mm, and the fly ash is 2 / g of secondary fly ash.

9. A cement pole, characterized in that: The durable concrete is prepared by the durable concrete as described in any one of claims 1 to 8.

10. The method for preparing cement poles according to claim 9, characterized in that: The following steps are involved: (1) The steel bars that have been treated with rust prevention are made into a steel bar skeleton and placed into a mold; (2) weighing raw materials according to the component proportions, adding sand, crushed stone and metal aggregate into a mixer, premixing for 2-3 minutes, then adding cement, fly ash and mineral powder into the mixer and dry mixing for 2-3 minutes, finally, adding polyurethane aqueous dispersion, rust inhibitor, water reducing agent, air entraining agent and water into the mixer, and continuing to stir for 20-40 minutes to obtain mixed concrete; (3) The mixed concrete prepared in step (2) is accurately weighed according to the amount required for the electric pole and accurately distributed through a delivery pump, and compacted by a centrifugal process. The electric pole after centrifugation is placed in a steam curing tank and left to stand for 3-5 hours to allow the concrete to reach an initial setting state; steam is then introduced into the tank at a heating rate of ≤25°C / h; the temperature in the tank is raised to 75-85°C, and the constant temperature is maintained for 4-6 hours, and then the steam is stopped. After 2-4 hours, the steam curing tank cover is opened to start natural cooling. When the mold temperature drops to a temperature difference of ≤30°C from the ambient temperature, the electric pole mold is opened and demoulding is performed; after demoulding, the electric pole is subjected to watering and moisture-maintaining maintenance for not less than 7 days to obtain a cement electric pole.